Arterial-Arteriolar Sclerosis Is Independently Associated With Poor Renal Outcome in IgA Nephropathy Patients - Dong, Lingqiu; Tan, Jiaxing; Li, Fangming; Wang, Siqing; Jiang, Zheng; Qin, Aiya; Zhong, Zhengxia; Zhou, Xiaoyuan; Tang, Yi; Qin, Wei (Frontiers in Medicine, 2021)
Aims: This study aimed to investigate the clinicopathological features and prognosis of IgA nephropathy with arterial-arteriolar sclerosis (AS) Methods: Patients with biopsy-proven IgA nephropathy from West China Hospital of Sichuan University were retrospectively enrolled. Clinicopathological features were collected. Patients were categorized based on the presence and the severity of the arterial-arteriolar sclerosis. All patients were regularly followed up until a composite endpoint. The correlation between arterial-arteriolar sclerosis and prognosis of IgA nephropathy was assessed. Results: A total of 1424 patients were recruited and followed for 60.0±28.7 months. Patients with arterial-arteriolar sclerosis tended to have older age, higher blood pressure, heavier proteinuria, higher serum creatinine, uric acid, and total triglyceride. Meanwhile, they were more likely to have a lower eGFR, hemoglobin, and albumin. At the end of follow-up, 126 patients in the AS group and 47 in the non-AS group had reached the composite endpoint (P<0.001). Arterial-arteriolar sclerosis was associated with the renal outcome (log-rank P<0.001) and was an independent risk factor for the progression of IgA nephropathy (P=0.049). The severity of arterial-arteriolar sclerosis was associated with renal outcomes (log-rank P<0.001) and there was a trend that it might serve as an independent risk marker for progression of IgAN. In subgroup analysis, patients presenting with arterial-arteriolar sclerosis and lower eGFR, albumin, and hemoglobin, or higher proteinuria, uric acid, and TG had a significant trend for a shorter time to reach the endpoint (log-rank P<0.001). Conclusions: Arterial-arteriolar sclerosis was commonly seen in IgA nephropathy patients and was independently associated with the poor prognosis. Key words: IgA nephropathy, arterial-arteriolar sclerosis, end-stage renal disease, renal survival, chronic kidney disease